PENGENALAN LAYANAN APLIKASI JAMSOSTEK MOBILE MELALUI VIDEO PROMOSI DAN BANNER PADA BPJS KETENAGAKERJAAN CABANG MAKASSAR - Sampe Pande, Jenica; Gunawan, Maylisa (Politeknik STIA LAN Makassar, 2023)
Jamsostek Mobile is the latest application from BP-Jamsostek, which provides services to its participants online. JMO has more complete features compared to previous applications, such as claim features, work accident reporting, co-marketing, and a network of service partners and branch offices. The purpose of this study was to create a promotional strategy using advertising media, namely videos and banners, in order to socialize the JMO application and formulate the impact of the Social Security Mobile (JMO) promotion using advertising media on BPJS Ketenagakerjaan participants. The results of the study showed that some people were more interested in seeing promotional videos on social media than through print media. This is because promotional videos are denser, clearer, and easier to understand, and the dissemination of information reaches the public faster. So that promotion through video media can quickly increase the number of consumers or users of a product or service within a company. The other promotional strategy used is the banner. The results of the study show that some people are interested in seeing promotions through banners. This is because banners are usually placed in public places that can be reached by everyone, and the dissemination of information is very fast. So that promotion through banners is effectively used to introduce products or services.